Rise of the Hyksos : Egypt and the Levant from the middle kingdom to the early second intermediate period - Mourad, Anna-Latifa, (Archaeopress Egyptology ;, 2015)
Manetho's obscure reference to a race of invaders has been a constant source of debate and controversy. But who are these invaders? They are named the 'Hyksos'. The Hyksos are correlated with the fifteenth dynasty of the second intermediate period, a time characterised by the destabilisation and regionalisation of the Egyptian state. Several scholars have pondered over their victory and rule in Egypt, from the manner in which they entered Egypt and the means with which they claimed the throne to their final expulsion from the land. This book assesses their rise to power, exploring the preliminary stages that enabled the Hyksos to gain control over a portion of Egyptian territory and thus to merit a small mention in Manetho's history.